EW 103 : tactical battlefield communications electronic warfare - Adamy, David (Artech House radar library., 2009)
The third book in the bestselling Artech House EW 100 series is dedicated entirely to the practical aspects of electronic warfare against enemy communication. Like its predecessors, EW 103 presents a series of highly informative and easy-to-comprehend tutorials, along with insightful introductory and connective material that helps you understand how each aspect fits together. From communications math (mainly simple dB formulas), receiving systems, and signals, to communications emitter location, interecept, and jamming, this comprehensive volume covers all the key topics in the field.